Feira livre e circuitos da economia urbana: um estudo da feira da Pedra, em São Bento (PB) - Santos, José Erimar dos (2012)
The Feira da Pedra is an extension of the open fair of São Bento in the State of Paraiba. It is a system of trade in textile goods produced by textile industry in manufacturing of hammocks and derivatives of this industry, present in some cities in the state of Paraiba and Rio Grande do Norte, as a survival strategy, inserted in the list of tertiary and retail of the urban economics of this city. It is thereby aimed to discuss about the urban economics, reflecting on the open fair system from the two circuits of urban economy, mainly in the context of the dynamics of the current period of geographic space, the technical-scientific-informational period, as the specific empirical object, the Feira da Pedra of São Bento (PB). For this, this research was carried out in two stages of operation: a) surveys of secondary data and b) primary data collection which were reported an operational triad: I) literature; II) documentary research, and III) research of field. The presence of the Feira da Pedra in São Bento has shown us one of the most important characteristics of this city, in order to present major economic, social and cultural benefits to the local population, and contribute to (re) production of sertanejo space, making lower part of the circuit of its urban economy. This activity has entailed several dynamics for urban space in this city, mainly because of attracting large numbers of people, carrying typical actions of its relationship with the urban space are são-bentense and built environment. Thus, its importance is not only a local and regional phenomenon, but also a cultural reference of a place in the geographical area of many paraibanos and norte-rio-grandenses subjects, as the case of this activity has brought to its weekly routine, this product resulting from the textile working of this area of Sertão Paraibano and Seridó Potiguar